Protective effects of the novel adenosine derivative WS0701 in a mouse model of posttraumatic stress disorder - Huang Zhong-lin; Liu Rui; Bai Xiao-yu; Zhao Gang; Song Jun-ke; Wu Song; Du Guan-hua (Acta Pharmacologica Sinica, 2016)
Zhong-lin HUANG1, Rui LIU1, Xiao-yu BAI1, Gang ZHAO1, Jun-ke SONG1, Song WU2, Guan-hua DU1, 2, * 1Beijing Key Laboratory of Drug Targets Identification and Drug Screening, Institute of Materia Medica, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing 100050, China; 2State Key Laboratory of Bioactive Substance and Function of Natural Medicines, Department of New Drug Research and Development, Institute of Materia Medica, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing 100050, China Aim: To investigate the effects of the novel N6-substituted adenosine derivative {(2R,3S,4R,5R)-3,4-dihydroxy-5-[6-[(4-hydroxy-3-methoxybenzyl)amino]-9H-purin-9-yl]tetrahydrofuran-2-yl} methyl decanoate (WS0701) on stress-induced excessive fear, anxiety, and cognitive deficits in a mouse model of posttraumatic stress disorder (PTSD). Methods: Molecular modeling approach combining quantum-polarized ligand docking (QPLD), MM/GBSA free-energy calculation and 3D-QSAR analysis was used to evaluate 24 compounds as dual AT1 and ETA receptor antagonists and to reveal their binding modes and structural basis of the inhibitory activity. Pharmacophore-based virtual screening and docking studies were performed to identify more potent dual antagonists. Results: WS0701 administration significantly alleviated fear, anxious behaviors and memory deficits in the mouse model of PTSD. Furthermore, WS0701 administration significantly reduced the stress-induced apoptosis of hippocampal neurons, and increased the Bcl-2/Bax ratio in the hippocampus. The positive control drug paroxetine exerted similar effects on PTSD-like behaviors and hippocampal neuron apoptosis in the mouse model of PTSD, which were comparable to those caused by the high dose of WS0701. Conclusion: WS0701 effectively mitigates stress-induced PTSD-like behaviors in mice, partly via inhibition of neuronal apoptosis in the hippocampus. Keywords: posttraumatic stress disorder; WS0701; adenosine; AMG-1; paroxetine; fear; anxiety; memory deficits; hippocampus; apoptosis; Bcl-2; Bax This study was supported by the International S&T Cooperation Projects (No 2009DFA32010), the National Scientific and Technological Major Project (2009ZX09102-003 and 2013ZX09J13102-05C), and the Special Foundation for Public Welfare Industry of Health (No 200902008), China. * To whom correspondence should be addressed. E-mail dugh@imm.ac.cn Received 2013-04-11 Accepted 2013-08-28